2020
DOI: 10.21203/rs.3.rs-117423/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intestinal Microbiota Shapes Gut Physiology and Regulates Enteric Neurons and Glia

Abstract: Background: The intestinal microbiota plays an important role in regulating gastrointestinal (GI) physiology in part through interactions with the enteric nervous system (ENS). Alterations in the gut microbiome frequently occur together with disturbances in enteric neural control in pathophysiological conditions. However, the mechanisms by which the microbiota regulates GI function and the structure of the ENS are incompletely understood. Using a mouse model of antibiotic (Abx)-induced bacterial depletion, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 73 publications
0
18
0
Order By: Relevance
“…Mice treated with antibiotics exhibit lower levels of colonic 5-HT and decreased Tph1 expression, 5,21 which parallel the findings of GF-associated deficits to the gut 5-HT system. Furthermore, these alterations in 5-HT levels result in functional changes to intestinal transit, as antibiotic-treated mice display slower whole gut transit [21][22][23][24] and slower colonic motility times 21,24 compared with controls. In addition, these functional deficits are accompanied by loss of enteric neurons.…”
Section: Direc T Mechanis Msmentioning
confidence: 99%
See 1 more Smart Citation
“…Mice treated with antibiotics exhibit lower levels of colonic 5-HT and decreased Tph1 expression, 5,21 which parallel the findings of GF-associated deficits to the gut 5-HT system. Furthermore, these alterations in 5-HT levels result in functional changes to intestinal transit, as antibiotic-treated mice display slower whole gut transit [21][22][23][24] and slower colonic motility times 21,24 compared with controls. In addition, these functional deficits are accompanied by loss of enteric neurons.…”
Section: Direc T Mechanis Msmentioning
confidence: 99%
“…In addition, these functional deficits are accompanied by loss of enteric neurons. 22 Interestingly, antibiotic-induced changes are reversible. Following reconstitution of the microbiota, mice display restored GI motility and enteric neurogenesis.…”
Section: Direc T Mechanis Msmentioning
confidence: 99%
“…In mice, loss of TLR4 signalling through genetic models, or as a consequence of microbiome depletion results in delayed gastrointestinal motility and reduces nitrergic neuronal counts, with subsequent in vitro experiments demonstrating that LPS exposure improves primary enteric neuron survival in a TLR4-dependent mechanism [ 133 ]. More recently, TLR4 activation by LPS administration during antibiotic treatment prevents the antibiotic-induced enteric neuronal loss in mice, but has no benefit if administered 14 days after antibiotic treatment, supporting a role for LPS-TLR4 signalling in enteric neuronal survival, but not in neurogenesis or differentiation [ 134 ]. TLR4 is also expressed by enteric glial cells [ 132 ], which protect enteric neurons and facilitate ENS signalling, and TLR4 knock-out mice exhibit altered ileal dysmotility and reactive gliosis [ 135 , 136 ].…”
Section: Tlrs and The Ensmentioning
confidence: 99%
“…Studies using germ-free mice, or mice treated with antibiotics to deplete the gut microbiota, have revealed that the microbiota shapes gut function and enteric neural control mechanisms. [140][141][142][143][144][145] Microbial dysbiosis is associated with a breakdown in epithelial barrier function and is associated with both local GI diseases, eg, IBD, and various systemic conditions, eg, obesity and diabetes. Investigations into the regulation of the ECS by the gut microbiome and vice versa are at an early stage, but some intriguing results have emerged that support the general hypothesis that the ECS regulates intestinal homeostasis through interactions with the microbiota.…”
Section: Reciprocal Regulation Of the Endocannabinoid System And The ...mentioning
confidence: 99%